TEOLOGI KELUARGA KUDUS - Paulinus Yan Olla (Studia Philosophica et Theologica, 2017)
The devotion to The Holy Family of Nazareth has marked Christian spirituality since the beginning of Christianity up to our days. Putting theological basis for this Christian devotion is the main concern of this work. One of the theological foundation for this devotion is the concept of “Terrestrial Trinity.” The Holy Family of Nazareth in this regard is a supreme image of the Trinity. The Catholic doctrine has applied this concept to all Christian families, but theologically it is in the life of The Holy Family, the Trinitarian life of love has its full expression. Finally, this work explores the spiritual dimensions of the Holy Family of Nazareth in the magisterium of the Church and in iconography as well. Devosi kepada Keluarga Kudus Nazaret menandai spiritualitas Kristiani sejak awal Kristianitas sampai saat ini. Peletakan dasar teologis untuk devosi Kristiani ini merupakan fokus utama dari karya tulis ini. Salah satu pondasi teologi dari devosi ini adalah konsep “Trinitas Terrestrial.” Keluarga Kudus Nazaret dalam pandangan ini merupakan gambaran tertinggi dari Trinitas. Doktrin Katolik mengaplikasikan konsep ini untuk semua keluarga Kristiani, tetapi secara teologis dalam hidup Keluarga Kudus, cinta dari kehidupan Trinitarian mempunyai ekspresi yang penuh. Pada akhirnya, karya tulis ini mengeksplorasi dimensi spiritual dari Keluarga Kudus Nazaret dalam magisterium Gereja dan juga ikonografi.